2007
DOI: 10.1007/s11256-007-0054-x
|View full text |Cite
|
Sign up to set email alerts
|

Education in the United States: Is it a Black Problem?*

Abstract: This review offers a critical analysis of John OgbuÕs Black American Students in an Affluent Suburb: A study of academic disengagement. In his study, Ogbu explains the Black-White achievement gap as one born from the cultural attitudes held by Black middle-class students toward academics. Despite Ogbu's intent to further the scholarly discussion on this issue, the study falls short and is itself replete with limitations. OgbuÕs utilization of a deficit-oriented modality and an unsound methodology, coupled with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…The causes of these attainment gaps are still a matter of debate (for the US, see Comeaux and Jayakumar 2007; for the Netherlands, see Severiens and Wolff 2009). Nevertheless, the conclusions that have thus far been reached on the basis of research carried out in the UK may well provide at least a basis for future discussion and investigation for colleagues elsewhere.…”
Section: Implications For Other Countriesmentioning
confidence: 99%
“…The causes of these attainment gaps are still a matter of debate (for the US, see Comeaux and Jayakumar 2007; for the Netherlands, see Severiens and Wolff 2009). Nevertheless, the conclusions that have thus far been reached on the basis of research carried out in the UK may well provide at least a basis for future discussion and investigation for colleagues elsewhere.…”
Section: Implications For Other Countriesmentioning
confidence: 99%
“…They concluded that the poor achievement of Black students was caused by structures and practices in the school itself. More crucially, Comeaux and Jayakumar (2007) provided a critical analysis of Ogbu's (2003) study. First, they argued that Ogbu had assumed that poor attainment was due to deficiencies within the students themselves and had ignored evidence of structural factors, such as institutional racism in the students' learning environment.…”
Section: Jte Richardsonmentioning
confidence: 99%
“…Finally, they argued that Ogbu had employed ideologically biased concepts of identity, culture and language and had uncritically accepted the principles and practices of White American culture as the norm. Tyson, Darity, and Castellino (2005) and Comeaux and Jayakumar (2007) claimed that poor attainment in ethnic minority students was due to the nature of their interactions with their teachers and other students. The present study was premised on the idea that such interactions are reduced in distance education in comparison with faceto-face education (Keegan 1990;Moore 1980), in which case their effects should be attenuated in the context of distance education.…”
Section: Jte Richardsonmentioning
confidence: 99%
“…Experts abound who support and oppose these ideas. Comeaux and Jayakumar (2007) maintained race and ethnicity are factors in every aspect of education in the United States. Johnson et al (2008) pointed out that all schools reflect the culture from which they were formed and all schools are created to maintain the culture of their creators.…”
Section: Discussionmentioning
confidence: 99%